Does film obey the laws of the mind? - Munsterberg, cognitivism and the films of Hussain Haniff / Norman Yusoff - Yusoff, Norman (UPENA, 2007)
This essay attempts at exposing Munsterberg's argument for the unique properties of cinema by focusing on the psychological responses of the viewer and on the aesthetic properties of film as a mental creation. The discussion seeks to examine the persuasiveness of Munsterberg's argument that "the photoplay obeys the laws of the mind rather than those of the outer world," for Munsterberg attempted at analogizing the cinematic devices to mental processes. In alignment with the paradigm shift in contemporary film theory (and academic film studies, in general), the essay will draw in connections with other film theorists in a manner that complements Munsterberg's arguments, as well as cognitive film theory. The second strand of my discussion entails analysis of Hussain Haniff's stylistic approaches to which Munsterberg's arguments are applied. This is to ascertain the relevance of Munsterberg's arguments which were put forth during the silent film era in relation to the study of Malay films directed by Hussain Haniff. Indeed, the films of Hussain Haniff have been widely acknowledged for accentuating cinematic styles which distinguish themselves from most films of the (studio) era.